PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS DISCOVERY LEARNING PADA MATERI PRISMA DAN LIMAS UNTUK SISWA KELAS VIII SMP - Dede Sumiati; Nahor Murani Hutapea; Putri Yuanita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Absrtract: The development of science and technology is very influential on the quality of human resources. Quality of human resources derived from the learning process, that is through education. Education is closely related to the development of the curriculum. The 2013 curriculum focuses on students' understanding and activity. The study is based on the limited learning tools of mathematics as a supporter of learning. This study aims to produce a learning device based on discovery learning mathematics on prism and limas material for students of class VIII junior high school that is valid and practical to use. This research is a development research with ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The results showed that the learning tools developed have been valid indicated by the results of design of learning implementation (RPP) and students activity sheet (LKS) assessment with the criterion "valid". Work sheet developed are practically demonstrated by the results of the students' assessment with the criteria of "very practical". The learning tools of mathematics developed have the following characteristics: (a) the learning activities contain the steps of the discovery learning model consisting of stimulation / stimulation, problem identification, data collection, data processing, verification, and conclusion; and (b) contains a scientific approach consisting of questioning, observing, questioning, collecting information, reasoning, and concluding.Keywords: Learning Tool, Discovery Learning, Curriculum 2013, Scientific Approach